Discovery of a new mitochondria permeability transition pore (mPTP) inhibitor based on gallic acid - José Teixeira; Catarina Oliveira; Fernando Cagide; Ricardo Amorim; Jorge Garrido; Fernanda Borges; Paulo J. Oliveira (Taylor & Francis Group, 2018)
Pharmacological interventions targeting mitochondria present several barriers for a complete efficacy. Therefore, a new mitochondriotropic antioxidant (AntiOxBEN3) based on the dietary antioxidant gallic acid was developed. AntiOxBEN3 accumulated several thousand-fold inside isolated rat liver mitochondria, without causing disruption of the oxidative phosphorylation apparatus, as seen by the unchanged respiratory control ratio, phosphorylation efficiency, and transmembrane electric potential. AntiOxBEN3 showed also limited toxicity on human hepatocarcinoma cells. Moreover, AntiOxBEN3 presented robust iron-chelation and antioxidant properties in both isolated liver mitochondria and cultured rat and human cell lines. Along with its low toxicity profile and high antioxidant activity, AntiOxBEN3 strongly inhibited the calcium-dependent mitochondrial permeability transition pore (mPTP) opening. From our data, AntiOxBEN3 can be considered as a lead compound for the development of a new class of mPTP inhibitors and be used as mPTP de-sensitiser for basic research or clinical applications or emerge as a therapeutic application in mitochondria dysfunction-related disorders.